Peningkatan Kemampuan Menganalisis Fenomena Sosial dengan Penerapan Model Problem Based Learning: Improved Ability to Analyze Social Phenomena by Applying Problem Based Learning Model - Imron, Ilmawati Fahmi; Aka, Kukuh Andri (Pedagogia : Jurnal Pendidikan, 2018)
Conducted on the students of UN PGRI Kediri on IPS learning, found some obstacles in the practice of IPS learning that many students who play games, then when the lecturer asked questions about social phenomena in the surrounding community, students are less responsive to the problems that occur today. In learning the students do a little questioning about social phenomena, they just sit, shut up, listen and many are out of the classroom. Students' learning outcomes about social phenomena are also less satisfactory. Seen from some grades of student assignment, still at 52% or below KKM (70%). Observing the constraints, the researchers identified that the ability to analyze the social phenomenon of students on IPS learning is low, because the use of learning models that are less in accordance with the study materials of social phenomena, so that students are tired in learning and find difficulties in understanding the content and less able to analyze the causes, further impacts, and solutions of social phenomena presented by lecturers. Based on the above, the researcher intends to conduct classroom action research to improve the ability to analyze social phenomena by applying Problem Based Learning model (PBL)